Comparison of Efficacy and Safety Outcome Among Tacrolimus Ointment, Cyclosporine, and Anti Histamine in Managing Patient with Allergic Conjunctivitis - Brenda Hayatulhaya; Lukman Edwar (Majalah Oftalmologi Indonesia, 2020)
Objective: To evaluate and compare the efficacy and safety between tacrolimus, cyclosporine ointment and anti-histamine as single therapy for allergic conjunctivitis. Methods: A comprehensive literature search was conducted through PubMed/MEDLINE, clinicalkey.com and ophtalmologyadvance.com databases. All studies included were interventional or observational reporting the efficacy of tacrolimus, cyclosporine, and antihistamine as monotherapy for all types allergic conjunctivitis. Outcome of this review included number of resolution, duration to resolution, recurrence and complications. Result: Eighteen studies were included in this study. Males predominated, with overall ratio ±2:1 compared to female. Most studies use objective signs and subjective symptom scoring before treatment, during follow up and after treatment for outcome measurement. In the antihistamine group, there was a decrease in itching and redness scores of about 33-75%, especially Bepostatinebesilate solution at a concentration of 1.5% Improvement in conjunctival hyperemia and complete resolution of papillary hypertrophy reported in tacrolimus and cyclosporine group, more than 50% reduction on symptoms and signs severity was found in all patients on tacrolimus and cyclosporine group. Conclusion: Tacrolimus and cyclosporine clinically improved allergic conjunctivitis. Topical cyclosporine and tacrolimus were suggested to be an effective and safe alternative therapy for resistant allergic conjunctivitis.